Decommissioning of fixed assets and land recovery: accounting and assessment - Orlova, V.; Kafka, S.; Riabkova, O. (Видавництво Львівської політехніки, 2019)
The existing provisions and regulations for the accounting of the written-off objects of the fixed assets and the working balances creation to cover the expenses of land restoration were investigated. Taking into consideration the peculiarities of the Ukrainian enterprises activity in the field of oil and gas industry, the problematic aspects within the accounting of the fixed assets and other non- circulating assets were investigated. The structure of the expected expenses for decommissioning of fixed assets and land restoration, that are the specific objects of the oil and gas industry enterprises, was determined. Based on the reasoning for structural expenses, the conceptual basis for the creation of accounting methodology with the emphasis on the contents of operations for funds creation for the provision of expenditure for the subsequent periods to finance economic operations for decommissioning of fixed assets and the restoration of land in the oil and gas industry. It has been proven in this article that creation of amounts of securities for such aims of the enterprise, should be identified in accordance with such criteria as the planned level of changes of the possible stock for oil and gas mining. It is argued that at each of the following stages of the mineral wealth exploitation, to recognize such liabilities in the accounting system are necessary, taking into account the risks, associated with the decommissioning of such assets. For the objective results provision, the general scientific methods of scientific knowledge, the specific methods of accounting and risk management methods were used.
Keywords: costs for decommissioning; provision; obligations; accounting; fixed assets; assessment; 657.471